Simultaneous Boron Ion-Channel/Growth Factor Receptor Activation for Enhanced Vascularization - Rico, Patricia; Rodrigo-Navarro, Aleixandre; de la Peña, Marcos; Moulisová, Vladimira; Costell, Mercedes; Salmerón-Sánchez, Manuel (Advanced biosystems, 2019)
Boron ion is essential in metabolism and its concentration is regulated by ion-channel NaBC1. NaBC1 mutations cause corneal dystrophies such as Harboyan syndrome. Here a 3D molecular model for NaBC1 is proposed and it is shown that simultaneous stimulation of NaBC1 and vascular endothelial growth factor receptors (VEGFR) promotes angiogenesis in vitro and in vivo with ultralow concentrations of VEGF. Human umbilical vein endothelial cells' (HUVEC) organization into tubular structures is shown to be indicative of vascularization potential. Enhanced cell sprouting is found only in the presence of VEGF and boron, the effect abrogated after blocking NaBC1. It is demonstrated that stimulated NaBC1 promotes angiogenesis via PI3k-independent pathways and that α5 β1 /αv β3 integrin binding is not essential to enhanced HUVEC organization. A novel vascularization mechanism that involves crosstalk and colocalization between NaBC1 and VEGFR receptors is described. This has important translational consequences; just by administering boron, taking advantage of endogenous VEGF, in vivo vascularization is shown in a chorioallantoic membrane assay.
Keywords: integrins; NaBC1; fibronectin; boron ion; VEGF; vascularization